Bridge modeling on the backwater effect due to arrangement and type of piers - Yap, Chee Kien (2013)
The existing of bridge piers in river waterways causes backwater effect where there is an increase in water level at upstream. During monsoon season at East Coast of Malaysia, the amount of water flow in upstream of bridge increases due to long duration and high intensity of rainfall that effectively increases the backwater amount. Hence, the excessive amount of backwater resulted in flooding to vicinity area. Therefore, a research was carried on the basis of laboratory experimental as to analyse the hydraulic profile and the significance of the backwater effect. The models incorporated different types and arrangements of piers for bridge model in three channel conditions (rectangular, floodplain and embankment channels) in subcritical flow. The results from this research suggested that the backwater measured was relatively higher than that computed backwater from equation where these values need to be reduced by considering the absolute surface roughness value for concrete material. In addition, it is shown that Ay/y3 values for square pier and a of 0.167 are relatively higher than circular pier and a of 0.083, respectively. With such findings enhance the knowledge of engineer by considering backwater effect in designing bridge which eventually reduces the flood events due to excessive backwater effect.